Management and prevention of soft tissue complications in implant dentistry. Issue 1 (1st February 2022) - Thoma, Daniel S.; Gil, Alfonso; Hämmerle, Christoph H. F.; Jung, Ronald E.
Abstract: The management and prevention of soft tissue complications is of key importance in modern implant dentistry and influences biologic and esthetic outcomes. The assessment of the soft tissue conditions from a quantitative and qualitative perspective should, therefore, be part of the overall treatment plan. Such an assessment dictates a potential indication as well as an ideal time point for additional soft tissue management. A proper risk assessment and management of the soft tissues at the planned implant site are of key importance prior to any implant‐related surgery. Cases with peri‐implant soft tissue complications generally involve: (a) a lack of attached and keratinized mucosa; (b) insufficient volume; (c) development of mucosal dehiscences; or (d) a combination of (a), (b), and (c). In case of soft tissue deficiencies, these should be addressed as early as possible to increase the predictability of the surgical interventions. This article reviews the main causes for peri‐implant soft tissue complications and presents different therapeutic options for the management of various clinical scenarios.